Predicting factors for readmission type 2 diabetes mellitus patients in Indonesia: A cross-sectional study - Husna, Cut; Mardhiah, Ainol; Fithria , Fithria; Putra, Ardia (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Readmissions negatively impact patient’s quality of life and increase health and care costs. Readmission among type 2 diabetes mellitus (T2DM) patients can be related to several factors, including age, gender, complications of diabetes, instability of blood sugar levels, diabetes education strategies, diet management, physical exercise, and therapy adherence. This study aims to identify the determinants of readmission of T2DM patients at the regional hospital of Aceh, Indonesia. Methods: The study employed a correlational design with a cross sectional approach. The sample was 184 T2DM readmission patients selected using an accidental sampling technique. Data was collected using several instruments: the Diabetes Early Readmission Risk Indicators (DERRI™) questionnaire, laboratory results of blood sugar levels, diabetes education strategies, United Kingdom Diabetes and Diet Questionnaire, International Physical Activity Questionnaire (IPAQ), Insulin Treatment Appraisal Scale (ITAS), and the readmission questionnaire. Data were analyzed using the Chi-square test and multiple logistic regression. Results: Data analysis revealed significant relationships between age (p=0.013), diabetes complications (p=0.000), unstable blood sugar levels (p=0.000), diabetes education strategies (p=0.000), diet management (p=0.000), and therapy adherence (p=0.000) with T2DM readmissions. No significant relationship was found for gender (p=0.073) or physical activity (p=0.430). Among all factors, diabetes complications were the strongest predictor of readmission (OR=5.330). Conclusions: The findings emphasize the importance of increasing patient independence in self-care to manage diabetes effectively. Stakeholders are encouraged to re-evaluate diabetes care strategies by optimizing discharge planning to address complications and reduce readmissions among T2DM patients.